EXPERIMENTAL STUDIES OF THE TISSUES REACTIONS IN THE RATS’ JAWS IN RESPOND TO THE NEW ROOT CANAL FILLING MATERIAL FOR THE TEMPORARY ROOT CANALS OBTURATION IN CHILDREN’s PERMANENT TEETH - Kostyuk, I.R.; Kostyuk, V.; Melnychuk, G.; Gavryliv, G.M. (World of Medicine and Biology, 2012)
Repair in the apical periodontium and periapical bone healing are the most important task of modern stomatology, therefore the development of the unused methods of the therapeutic treatment are on the growth as there is no absolute periapical hard tissues regeneration after endodontic interferences on permanent teeth in children. We have exhibit and investigate the Calcium Hydroxide Comfrey containing Paste in prospect for temporary root canals obturations in permanent teeth in children. Morphological examinations on the rats have proved that the paste is not toxic to the bone and to the soft surrounding mandibular tissues of the animals after the operation as well as maximizes the anti-inflammatory treatment and bone regeneration.